The Cultural Heritage related to the Spread of Christianity as a Tourist Attraction in Humbang Hasunduntan Regency, North Sumatra - Rita Margaretha Setianingsih (Tourism, Hospitality And Culture Insights Journal, 2021)
The area of ​​Humbang Hasundutan Regency is 251,765.93 Ha. Consists of 10 (ten) Districts, 153 (one hundred and fifty-three) Villages and 1 (one) Kelurahan. There are 10 sub-districts, namely Pakkat District, Onanganjang District, Sijamapolang District, Lintongnihuta District, Paranginan District, Doloksanggul District, Pollung District, Parlilitan District, Tarabintang District and Baktiraja District. The tourist attractions in the Humbang Hasundutan area are several cultural heritages in the form of church remains, both Catholic churches and Protestant churches. The church was built from 1937 to 1950 where the spread of Christianity began. There are several cultural heritages related to the spread of Christianity as a tourist attraction in Humbang Hasundutan Regency, North Sumatra, namely (1) the HKPB Sabungan in Lintongnihuta; (2) HKBP Sihorbo Tanjung in Rura Tanjung Village, Pakkat District; (3) HKBP Pargodungan in Lumban Tobing, Dolok Sanggul; (4) the Catholic Church Maria Bunda Kerahiman Ilahi in Siniang Laksa, Lumban Tonga-tonga, Pakkat District; and (5) St. Fidelis Church in Dolok Sanggul and several other churches. The results of the study will show that several Cultural Heritage Related to the Spread of Christianity can be used as a tourist attraction in Humbang Hasundutan Regency, North Sumatra, while the intention is so that the community in this case also the students know that Humbang Hasundutan has a high cultural heritage value which can be used as a tourist attraction or a historical and cultural tourist destination that can be visited by domestic and foreign tourists.